Study of Ion Exchange Equilibria of Uni-Univalent Ions on Duolite A-113 - Lokhande, R.S.; H. Dole, Madhavi (Asian Journal of Chemistry, 2010)
The exchange capacity of an ion exchange resin has been of considerable utility in scientific research and industry. The exchange capacity depends upon several factors like capacity, nature, concentration and temperature etc. It will be therefore useful in qualitative assessment of an ion exchange resin for its utility in a stipulated process and also in assessing its efficiency in several ion exchange process. The present work is an attempt to study an ion exchange equilibria on an exchange Duolite A-113.